2022
DOI: 10.1007/s00211-022-01291-2
|View full text |Cite|
|
Sign up to set email alerts
|

Rigorous numerics for nonlinear heat equations in the complex plane of time

Abstract: In this paper, we introduce a method for computing rigorous local inclusions of solutions of Cauchy problems for nonlinear heat equations for complex time values. The proof is constructive and provides explicit bounds for the inclusion of the solution of the Cauchy problem, which is rewritten as a zero-finding problem on a certain Banach space. Using a solution map operator, we construct a simplified Newton operator and show that it has a unique fixed point. The fixed point together with its rigorous bounds pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…There are five time scales that need to be considered. Setting w = w 0 + ϵw 1 + ϵ 2 w 2 + • • •, where w 0 (x, 0) = cos x, w k (x, 0) = 0, k ≥ 0, one obtains a sequence of linear PDEs: (23) and (24).…”
Section: Appendix D Analysis Of Solutions With Small-amplitude Initia...mentioning
confidence: 99%
See 1 more Smart Citation
“…There are five time scales that need to be considered. Setting w = w 0 + ϵw 1 + ϵ 2 w 2 + • • •, where w 0 (x, 0) = cos x, w k (x, 0) = 0, k ≥ 0, one obtains a sequence of linear PDEs: (23) and (24).…”
Section: Appendix D Analysis Of Solutions With Small-amplitude Initia...mentioning
confidence: 99%
“…Other complex-plane studies of the NLH have been reported in [22,23]. In both papers the equation was studied numerically in the complex t-plane.…”
Section: Introductionmentioning
confidence: 99%